Parafia miejscem wychowania do pokoju - Lipiec, Dariusz Andrzej (Verbum Vitae, 2016)
The Church was given the task of guiding Her members in the ways of peace. The parish plays a special role in realizing this mission, since it is the place where the individual meets God in His word, in the Sacraments, in prayer, and in brotherly love. In the parish, education in the value of peace is implemented first by building unity between the believers on the basis of brotherly love. It is also achieved through the deepening of one's awareness of and personal responsibility for peace, as well as by fostering the attitudes that support the building of unity and peace. The process of instructing and guiding believers toward peace is carried out by both the clergy and the laity, especially through families and members of religious associations.